Characterization of autoimmune inflammation induced prostate stem cell expansion. Issue 14 (14th July 2015) - Wang, Hsing‐Hui; Wang, Liang; Jerde, Travis J.; Chan, Bin‐Da; Savran, Cagri A.; Burcham, Grant N.; Crist, Scott; Ratliff, Timothy L.
<x xml:space="preserve">Abstract</x> BACKGROUND The presence of inflammation in prostate cancer (PCa) and benign prostate hyperplasia (BPH) has been well described but the cellular mechanisms by which inflammation modulates the prostate are currently unclear. Prostate stem cells (PSC) not only maintain prostate homeostasis but also are considered to be the cell of origin of PCa and an important contributor to BPH. However, the impact of inflammation on PSC is not well understood. Therefore, we initiated studies to evaluate the effect of inflammation on PSC. METHOD Ovalbumin specific CD8+ T cells were intravenously delivered to intact and castrated prostate ovalbumin expressing transgenic‐3 (POET‐3) mice to induce inflammation. Lin (CD45/CD31)−Sca1+CD49f+ cells (LSC) and progenitor cells within LSC were determined by flow cytometry. Sorted LSC were subjected to a prostate sphere forming assay to evaluate PSC clonal propagation, proliferation, immediate differentiation, and self‐renewal ability. Density of individual spheres was measured by a cantilever‐based resonator weighing system. Morphology and characterization of prostate spheres was determined by hematoxylin and eosin (H&E) staining and immunohistochemistry (IHC). Finally, immediate PSC differentiation in sphere formation was determined by immunofluorescence for epithelial cytokeratin markers cytokeratin (CK) 5 and CK8. RESULT Data presented here demonstrate a significant expansion of the proliferative (BrdU+) LSC population, including CK5+, p63+, CK18+ cells, as well as intermediate cells (CK5+/CK8+) in inflamed prostates. Histological images reveal that PSC from inflamed prostates produce significantly larger spheres, indicating that the enhanced proliferation observed in LSC is sustained in vitro in the absence of inflammatory mediators. In addition, cultures from inflamed PSC yielded increased number of tubule‐like spheres. These tube‐like spheres grown from PSCs isolated from inflamed mice exhibited stratification of a CK8+ luminal‐like layer and a CK5+ basal‐like layer. Notably, the numbers of spheres formed by inflamed and non‐inflamed PSC were equal, suggesting that even though proliferation is enhanced by inflammation, the homeostatic level of PSC is maintained. CONCLUSION Induction of inflammation promotes PSC expansion and immediate differentiation through highly proliferative progenitor cells while the homeostasis of PSC is maintained. Prostate 75:1620–1631, 2015. © 2015 The Authors. The Prostate, published by Wiley Periodicals, Inc.